Cantigas de Santa Maria : an anthology - Alfonso X, King of Castile and Leon, 1221-1284 (MHRA critical texts, 2015)
The Cantigas de Santa Maria, commissioned by King Alfonso X of Castile (r. 1252-1284), are one of the largest medieval vernacular collections of lyric and narrative verse in praise of the Blessed Virgin Mary. The 419 poems in Galician-Portuguese, the unchallenged language of troubadour verse in medieval Western Iberia, include 357 stories of miracles of the Virgin, interspersed with praise songs, hymns, and poems relating to her feast days. The poems, some of which were composed by Alfonso himself, were set to music and preserved in four regal manuscripts, two of which added full-page illustrative miniatures providing a parallel visual narrative. This makes the Cantigas a unique master work of medieval Hispanic poetry, iconography, music and manuscript culture. This Anthology presents the texts of 45 Cantigas de Santa Maria, together with the verse prologue to the collections, in a new critical edition designed for use both by students and scholars and by performers and their audiences. The critical apparatus includes full metrical interpretations and the captions of the illustrative miniatures. The edition is linked to the Cantigas de Santa Maria Databasewhich contains full information on the texts and their sources.